Mechanical Carbohydrate Sensors Based on Soft Hydrogel Particles1. Issue 23 (24th April 2013) - Pussak, Daniel; Ponader, Daniela; Mosca, Simone; Ruiz, Salomé Vargas; Hartmann, Laura; Schmidt, Stephan
<x xml:space="preserve">Abstract</x> Elastic sensors: A simple method is presented for the measurement of specific biomolecular interactions with soft colloidal hydrogel particles (SCPs) as sensors. Carbohydrate/lectin interactions (see picture; green: carbohydrate molecules) were studied by optical detection of the mechanical deformation of the particles on a lectin surface. The affinity of various carbohydrate inhibitors could also be readily determined.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>